Veterans' response to an automated text messaging protocol during the COVID-19 pandemic. (4th July 2020) - Saleem, Jason J; Read, Jacob M; Loehr, Boyd M; Frisbee, Kathleen L; Wilck, Nancy R; Murphy, John J; Vetter, Brian M; Herout, Jennifer
Abstract: The US Department of Veterans Affairs (VA) is using an automated short message service application named "Annie" as part of its coronavirus disease 2019 (COVID-19) response with a protocol for coronavirus precautions, which can help the veteran monitor symptoms and can advise the veteran when to contact his or her VA care team or a nurse triage line. We surveyed 1134 veterans on their use of the Annie application and coronavirus precautions protocol. Survey results support what is likely a substantial resource savings for the VA, as well as non-VA community healthcare. Moreover, the majority of veterans reported at least 1 positive sentiment (felt more connected to VA, confident, or educated and/or felt less anxious) by receiving the protocol messages. The findings from this study have implications for other healthcare systems to help manage a patient population during the coronavirus pandemic.